2011
DOI: 10.1007/s00122-011-1745-y
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of genomic selection in European maize elite breeding populations

Abstract: Genomic selection is a promising breeding strategy for rapid improvement of complex traits. The objective of our study was to investigate the prediction accuracy of genomic breeding values through cross validation. The study was based on experimental data of six segregating populations from a half-diallel mating design with 788 testcross progenies from an elite maize breeding program. The plants were intensively phenotyped in multi-location field trials and fingerprinted with 960 SNP markers. We used random re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
236
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 257 publications
(264 citation statements)
references
References 30 publications
23
236
3
2
Order By: Relevance
“…It would then be required to have an important coverage of the genome to capture ancestral LD, otherwise the reliability would be overestimated as discussed before. Breeders are also interested in applying genomic selection in multifamilial populations (Albrecht et al 2011;Zhao et al 2012). Albrecht et al (2011) showed that in such situations the prediction reliabilities are highly dependent on the composition of the calibration set.…”
Section: Discussionmentioning
confidence: 99%
“…It would then be required to have an important coverage of the genome to capture ancestral LD, otherwise the reliability would be overestimated as discussed before. Breeders are also interested in applying genomic selection in multifamilial populations (Albrecht et al 2011;Zhao et al 2012). Albrecht et al (2011) showed that in such situations the prediction reliabilities are highly dependent on the composition of the calibration set.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that prediction accuracy is impaired when performing genomic selection across connected biparental populations (Zhao et al 2012;Riedelsheimer et al 2013). This may be explained at least partially by epistatic effects as the genetic relatedness across connected populations may be better exploited by modeling epistasis in addition to additive effects.…”
Section: Enhancing Prediction Accuracy Across a Biparental Populationmentioning
confidence: 99%
“…The obvious advantages of GS over traditional MAS have been successfully proven in animal breeding [116]. Rapid evolution of sequencing technologies and HTP SNP genotyping systems are enabling generation and validation of millions of markers, giving a "cautious optimism" for successful application of GS in breeding for complex traits [117][118][119][120].…”
Section: Implementation Of Snp Markers In Plant Breedingmentioning
confidence: 99%